Contributors to disease‐specific health knowledge in adults with congenital heart disease: A correlational study. (27th September 2018) - Saef, Joshua; Sodhi, Sandeep; Tecson, Kristen M.; al Rashida, Vanessa; Mi Ko, Jong; White, Kamila S.; Ludbrook, Philip A.; Cedars, Ari M.
Abstract: Objective: Growth in the adults with congenital heart disease (ACHD) population represents a challenge to the health care infrastructure. As patients with chronic disease are increasingly held accountable for their own care, contributors to disease‐specific health knowledge, which are known to correlate with patients' participation in care, merit investigation to design patient‐focused interventions. Design: We conducted a single‐site, cross‐sectional study of ACHD patients. Investigators retrospectively gathered clinical data as well as psychometric and health status assessments completed at the time of enrollment. Outcome Measures: We investigated the impact of clinical and psychological variables on Leuven Knowledge Questionnaire for Congenital Heart Diseases health knowledge composite scores (HKCS). Variables with significant associations were considered in a stepwise multivariable regression model to determine which combination of variables jointly explained variability in HKCS. Results: Overall HKCS was associated with the number of prior cardiac surgeries ( r = 0.273; 95% CI: 0.050‐0.467; P = .016), perceived stress ( r = 0.260; 95% CI: 0.033‐0.458; P = .024), SF‐36 emotional well‐being ( r = −0.251; 95% CI: −0.451, −0.024; P = .030), history of noncardiac surgery ( P = .037), cirrhosis ( P = .048), and presence of implantable cardioverter‐defibrillator ( P = .028). On multivariable modeling, only the number of cardiac surgeries was found to correlate with HKCS. Conclusions: While univariate correlations were found between HCKS and several other clinical and psychological variables, only number of prior cardiac surgeries independently correlated with disease‐specific health knowledge in ACHD patients. These results suggest that clinical and psychological variables are not impediments to disease‐specific health knowledge.